Dietary Supplementation With Yucca Alleviates Heat Stress in Growing Broilers Exposed to High Ambient Temperature - Luo, Jing Jing; Chen, Wei; Qu, Hao; Liu, Yuan Qing; Luo, Cheng Long; Ji, Jian; Shu, Ding Ming; Wang, Jie (Frontiers in Veterinary Science, 2022)
Yucca contains high a content of saponin that has a glucocorticord-like effect in animals, e.g., anti-inflammation and anti-microbiota. The objective of the present study was to test the hypothesis that dietary supplementation of yucca powder may alleviate heat stress and improve growth performance of growing broilers subjected to cycling high ambient temperature. A total of 240 male broiler chicks (yellow feathered chicken) aged 28 days, with body weight (BW) of 792 ± 43.7 g, were randomly allocated to one of four treatments (6 replicates per treatment): control (normal temperature, 24 ± 2°C, 24 h), fed diets supplemented with 100 mg/kg yucca under normal temperature (Y), high ambient temperature exposure (HT, 34 ± 2°C, 11 h), fed diets supplemented with 100 mg/kg yucca (HT+Y) under high ambient temperature. After 7 days of adaption, the experiment was conducted for 4 weeks (aged 28–56 days). HT significantly reduced feed intake, BW, and average daily gain (ADG) of broiler, but yucca improved the feed intake under HT condition. Yucca supplementation reduced (P < 0.05) the HT-induced increase in temperature of rectum and leg skin. Supplementation of yucca increased the hypothalamic mRNA expression of TRPV2, TRPV4, and TRPM8 (P < 0.05). Yucca reduced (P < 0.05) the plasma lipid oxidation product malondialdehyde (MDA), but did not affect the activities of antioxidant enzyme superoxide oxidase (SOD) and glutathione peroxidase (Gpx). Yucca did not affect the plasma neuro peptide Y (NPY), which was reduced by HT, yucca reduced circulation cholecystokinin (CCK) and hypothalamic mRNA expression of CCK. Supplementation of yucca increased the mRNA expression of both heat and cool sensing receptors. The results of the present study indicate that yucca could improve antioxidant status and attenuate the heat stress response by regulating hypothalamic temperature-sensing genes in growing chickens. Besides, yucca supplementation improved feed intake probably through modulating CCK in growing broilers under high ambient temperature.